USE OF PROVERBS IN THE EDUCATIONAL PROCESS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article we will get acquainted with examples of folklore. We provide examples of proverbs to give a broader idea of understanding. Of course, proverbs have a great role and significance in the education process. In the process of mutual communication, we often use folk proverbs to prove our point. This helps us make our speech beautiful, attractive and authentic. Learning and teaching such proverbs gives our youth a sense of respect for their nation and a sense of pride in their hearts.